2012
DOI: 10.1007/978-94-007-5179-8_10
|View full text |Cite|
|
Sign up to set email alerts
|

Natural and Artificial Proteins Containing Cadmium

Abstract: This chapter describes an approach using designed proteins to understand the structure, spectroscopy, and dynamics of proteins that bind Cd(II). We will show that three-stranded coiled coils (3SCCs) based on the parent peptides TRI (Ac-G(LKALEEK)(4)G-NH(2)) or GRAND (Ac-G(LKALEEK)(5)G-NH(2)) have been essential for understanding how Cd(II) binds to thiolate-rich environments in proteins. Examples are given correlating physical properties such as the binding constants or deprotonation constants relating to stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“… 8 11 This can include the hydration state of a coordinated metal ion, a crucial parameter for MRI. 5 , 12 14 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 8 11 This can include the hydration state of a coordinated metal ion, a crucial parameter for MRI. 5 , 12 14 …”
mentioning
confidence: 99%
“…Though a range of different structural motifs have been studied, including β-sheets and mixed α/β-motifs, the majority of work has focused on coiled coils, in which multiple α-helices are supercoiled around one another. Metal ion binding sites have been successfully engineered into the interior of these structures, and one can take advantage of various design features to alter the metal ion coordination chemistry. This can include the hydration state of a coordinated metal ion, a crucial parameter for MRI. ,− …”
mentioning
confidence: 99%
“…The design of Zwit YK-C was guided by the previously reported structure of Zwit-YK (Figure 1 A), a β 3 -peptide bundle possessing well-ordered tertiary structure and superior thermal stability, 9 and the large body of research on α-peptide assemblies that bind Cd(II). 21 Examination of the Zwit-YK X-ray structure suggested that addition of a single β-homocysteine (β-Cys) residue to the Zwit-YK C-terminus would result in an octameric bundle containing two or four copies of two stereochemically and electrostatically distinct two-coordinate metal binding sites (Figure 1 B,C). One site is formed at the termini of two parallel helices and is repeated four times per bundle; the other is formed at the perpendicular interface of two helices from opposite halves of the bundle, and is repeated twice.…”
mentioning
confidence: 99%